Perancangan Aplikasi Midori Clon (Midori Class Online) Berbasis Mobile dengan Metode Design Thinking - Farel Atalla Muhammad Dafa; Ina Sholihah Widiati (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Online learning is widely used by various groups, especially in higher education/schools. Online learning has many benefits for students and lecturers due to its practical and flexible learning process. However, there are complaints in online learning, such as students having difficulty understanding the material shared by lecturers and the lack of interaction between lecturers and students, making the lessons monotonous and boring. Students also cannot review the targeted lecturers. Therefore, the Midori Clon application was created to address students' problems in online learning. The application design was developed using the Design Thinking method. The Midori Clon application offers several advantages, including a Live Video feature for more interactive sessions between students and lecturers, a Bot feature to summarize materials and translate languages, and a Lecturer Review feature to review the targeted lecturers. With these advanced features, it is expected that online learning issues can be resolved and online learning can meet the desired expectations.